Collage-based narratives of mothers of third culture kids: the in-between space of transnational families in the UAE - Dillon, Anna Marie; Ali, Tabassim (Frontiers in Sociology, 2024)
This study delves into the lives of transnational families in the UAE, exploring their complex identities using a visual research approach known as the Collage Life Elicitation Technique (CLET). Both the topic and the methodology are framed within a theoretical lens of Verstehen (understanding) with a view to further exploring the lives of transnational families in the context of a pragmatic phenomenology and within the setting of the UAE as a rentier state. The lives of families such as these are characterized by a cross-cultural lifestyle, high mobility and expected repatriation. This paper presents narratives of eight transnational families in the UAE as expressed by the mother of each family unit, and seeks to expand on how these mothers view the identity of their families as expatriates living in the UAE. Findings indicate that these families navigate an intricate world where they are neither entirely of their host country nor of their passport country. The family unit plays a pivotal role in these families’ lives, acting as a bridge between their host culture and their home culture, serving as a nucleus for their evolving identities.